Histopathological Effect of Extracellular Products of Clinical Isolates of Pseudomonas aeruginosa on Mice Lungs. (World Journal of Experimental Biosciences, 2023)
The bacterial secretions into the growth medium that are produced as a result of the dynamics of growth and death of bacteria such as proteins, nucleic acids, and polysaccharides stimulate inflammatory response. The effect of extracellular bacterial secretions that are released by bacteria during growth on inflammatory response as well as the body’s tissues is not clear. The current study aims to highlight the effect of sterile bacterial secretion (IBS) of clinical isolate Pseudomonas aeruginosa on lung tissue. Here, P. aeruginosa was isolated from urine and grown on Luria-Bertani (LB) broth for a day, and IBSs were collected after filtration using a Millipore filter. These materials were administered to the experimental mice intranasally (i.n.). The tissue sections of the mouse lungs and the number of leukocytes in the bronchoalveolar lavage (BAL) were examined. The histological sections showed an increase in the leukocyte infiltration into the alveoli cavity and walls was seen as early as 4 h post-installation, and this continued until the second day. However, at 72 post instillation, it was found that the lung tissue had almost completely recovered and returned to its normal shape. The study also showed an increase in the number of Leukocytes number in BAL of mice that were given the IBS as early as 4 h post instillation this increase continued until 72 h. The results showed the effect of IBS in stimulating a safe inflammatory response in the lungs of mice, and this could help in the possibility of using these materials in the future to increase the immunostimulation of weak immunostimulatory antigens.